Triple-a supply chain management for automobile industry: a case study of Renault Samsung Motors - Wooyoung Jeong; Minyoung Park; Jung Ung Min (Journal of International Logistics and Trade, 2009)
This paper presents a case study of Renault Samsung Motors (RSM) that recently encounters dynamic changes unveiling various opportunities and challenges due to increasing complexity of the supply network with growing sales volume, diversifying models, and intensifying global competition. Such competitive environment puts constant pressure on the logistics operations to reduce supply costs and lead time, but the RSM has not been paying much attention to aligning interests of supply chain partners. In 2007, RSM’s effort to build partnership with new 3PLs turned abortive due to their unexpected default on the contract throwing RSM into confusion and disruptions. In this study, the problem was investigated by examining route planning process and incentive scheme of 3PL, and an optimization model was constructed to evaluate the performance of existing 3PL operation. The results indicate that transportation cost can be reduced by relocating consolidation centers, utilizing regional terminal and redesigning routing sequence. However, the research found that the key to successful implementation of the optimized solutions is in designing effective incentive system that induces partners to participate in continuous improvement initiatives.